Analysis of consumer preferences towards digital marketing and its implications on the competitive advantage of SMEs in Banyuasin Regency - Hadiwijaya, Hendra; Yustini, Tien (Annals of Human Resource Management Research, 2023)
Purpose: The purpose of this research is to analyze consumer preferences towards digital marketing and its implications for the competitive advantage of Small and Medium Enterprises (SMEs) in Banyuasin Regency. Research Methodology: The population of this study consists of consumers of SMEs residing in the Banyuasin Regency. Random sampling was used to select respondents, with a sample size of 150 respondents. The data analysis technique used in this research was Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique. Results: Consumer preferences have a positive and significant influence on the competitive advantage of SMEs in Banyuasin Regency. Digital marketing acts as an intermediary factor between consumer preferences and competitive advantage. SMEs can expand their market share and achieve success in the digital market by understanding consumer preferences and implementing effective digital marketing strategies. Limitations: Each region has unique characteristics and local context. Factors such as culture, customs, local preferences, and technological infrastructure can influence consumer preferences and the competitive advantage. Contribution: This research provides valuable insights to SMEs in the Banyuasin Regency regarding consumer preferences for digital marketing. By understanding consumer preferences, SMEs can develop more effective marketing strategies and optimize the use of digital platforms to enhance their competitive advantage. Novelty: The novelty of this research lies in emphasizing the implications of digital marketing on the competitive advantage. This research identifies factors that can enhance the competitive advantage of SMEs through the implementation of appropriate digital marketing strategies. It provides practical contributions to SMEs facing an increasingly competitive market.